The role of initial teacher training in the process of building pedagogical knowledge - Suckel Gajardo, Marcela (2020)
This essay is articulated based on the process of construction of pedagogical knowledge that teachers build in training within the framework of Initial Teacher Training (FID). The process of building knowledge is articulated as a complex action, of self-elaboration and self-organization, linked to life trajectories, practical training and the relationship between theory and practice associated with IDF. In this scenario of initial training, reflection is one of the most important moments of the action research process by allowing to investigate the meaning of the reality studied and achieve some abstraction or theorization. From the above, incipient and differentiating aspects have been found in the different levels of initial training. From the IDF, the process of knowledge building is approached through the phases of Research-Action: diagnosis, it is deepened in themes circumscribed to the social and pedagogical field; design, sequences of learning activities with a focus on students are prepared; implementation of activities that closely link the context and student culture. The reflexive processes from the IDF, in association with the practical training of future teachers, would constitute a first approach to the educational trajectories of teachers in training, and would contribute to unlearning ways of acting and pedagogical reasoning to access spaces for analysis and problematization.